Preparation and immunogenicity of gold glyco-nanoparticles as antipneumococcal vaccine model. (January 2017) - Vetro, Maria; Safari, Dodi; Fallarini, Silvia; Salsabila, Korrie; Lahmann, Martina; Penadés, Soledad; Lay, Luigi; Marradi, Marco; Compostella, Federica
Aim: Nanotechnology-based fully synthetic carbohydrate vaccines are promising alternatives to classic polysaccharide/protein conjugate vaccines. We have prepared gold glyco-nanoparticles (GNP) bearing two synthetic carbohydrate antigens related to serotypes 19F and 14 of Streptococcus pneumoniae and evaluated their immunogenicity in vivo .Results: A tetrasaccharide fragment of serotype 14 (Tetra-14), a trisaccharide fragment of serotype 19F (Tri-19F), a T-helper peptide andd -glucose were loaded onto GNP in different ratios. Mice immunization showed that the concomitant presence of Tri-19F and Tetra-14 on the same nanoparticle critically enhanced the titers of specific IgG antibodies toward type 14 polysaccharide compared with GNP exclusively displaying Tetra-14, while no IgG antibodies against type 19F polysaccharide were elicited.Conclusion: This work is a step forward toward synthetic nanosystems combining carbohydrate antigens and immunogenic peptides as potential carbohydrate-based vaccines. Graphical abstract: